Peningkatan Kompetensi Tenaga Pendidik Melalui in House Training di SMK Muhammadiyah Parung-Kabupaten Bogor - Irfan Rizka Akbar; Mitri Nelsi; Indra Januar Rukmana (Jurnal Ilmiah Wahana Pendidikan, 2022)
This research is qualitative. Data was collected using test and interview methods. This study aims to analyze the implementation of improving teacher competence at SMK Muhammadiyah Parung, to find out the method of increasing technology updates for educators at SMK Muhammadiyah Parung, and to find out how to change the learning method from fix mindset to a growth mindset for educators at SMK Muhamadiyah Parung. The research subjects were teaching staff or teachers at SMK Muhammadiyah Parung by taking 3 teachers as samples. In this study, the teachers were interviewed to see their performance process in teaching. With the development and improvement of competence at SMK Muhammadiyah Parung through IHT, it gives good things to teachers or educators, and schools and even has a positive impact on students who are the target of the nation's generation of graduates. IHT activities carried out at SMK Muhammadiyah Parung by utilizing the latest technology, provide new learning and open new ways to developing interesting and not boring learning methods. This also has a good effect on students and provides a good description of the school from the point of view of the surrounding community because the good and bad of schools are very quickly distributed by students. IHT activities also provide understanding for educators and change the fixed mindset system into a growth mindset. This will continue to be able to develop educators to be much better than before.